2023
DOI: 10.1021/acs.langmuir.3c01699
|View full text |Cite
|
Sign up to set email alerts
|

Alkylamine-Grafted Molybdenum Disulfide Nanosheets for Enhanced Dispersion Stability and Lubricity Properties

Guxia Wang,
Changxing Yang,
Qingyan Bai
et al.

Abstract: The unique structure and ultralow interlayer shear strength give molybdenum disulfide (MoS2) materials a broad prospect for energy savings, economic benefits, and extended operating life of lubrication systems. Herein, we prepared an effective integration strategy to prepare novel small-sized and chemically grafted MoS2 to solve the problems of poor dispersibility and easy agglomeration of MoS2. The MoS2 powder was stripped and oxidized to generate active centers using acid oxidation and high-speed ultrasonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Meng et al [125] analyzed the lubrication mechanism using molecular dynamics simulations, which showed that an increase in normal pressure promotes interlayer slip and reduces the friction coefficient between the MoS 2 nanosheets. Wang et al [126] used alkylaminegrafted MoS 2 oxide nanosheets (MoS 2 -O-OLA) dispersed in 15# industrial white oil for friction experiments, confirming that MoS 2 -O-OLA nanosheets exhibited better friction and wear resistance, resulting in a significant reduction of friction (36.2%) and wear (22.4%) by 0.02 wt% MoS 2 -O-OLA nanosheets as compared to pure 15# industrial white oil. MoS 2 -O-OLA nanosheets played an important role in improving tribological properties by generating interlayer slip at the steel ball contact interface, resulting in surface protection and a uniform oil film.…”
Section: Shear Slipmentioning
confidence: 91%
“…Meng et al [125] analyzed the lubrication mechanism using molecular dynamics simulations, which showed that an increase in normal pressure promotes interlayer slip and reduces the friction coefficient between the MoS 2 nanosheets. Wang et al [126] used alkylaminegrafted MoS 2 oxide nanosheets (MoS 2 -O-OLA) dispersed in 15# industrial white oil for friction experiments, confirming that MoS 2 -O-OLA nanosheets exhibited better friction and wear resistance, resulting in a significant reduction of friction (36.2%) and wear (22.4%) by 0.02 wt% MoS 2 -O-OLA nanosheets as compared to pure 15# industrial white oil. MoS 2 -O-OLA nanosheets played an important role in improving tribological properties by generating interlayer slip at the steel ball contact interface, resulting in surface protection and a uniform oil film.…”
Section: Shear Slipmentioning
confidence: 91%
“…The S atoms exposed on the crystal surface have strong adhesion to the metal surface, making MoS 2 well adhered to the metal surface (Hu et al , 2010). Numerous studies have confirmed the excellent performance of MoS 2 as a lubricant additive in reducing friction (Xu et al , 2015a; Hu et al , 2010; Wu et al , 2018; Liu and Zhou, 2017; Tang et al , 2013; Wang et al , 2023). However, MoS 2 nanoparticles are prone to agglomerate and settle in solution due to their large surface energy and specific surface area, which in turn affects their dispersion stability, lubricity and heat transfer properties (Hou et al , 2020; Sahoo and Biswas, 2010).…”
Section: Introductionmentioning
confidence: 93%
“…The S atoms exposed on the crystal surface have strong adhesion to the metal surface, making MoS 2 well adhered to the metal surface (Hu et al, 2010). Numerous studies have confirmed the excellent performance of MoS 2 as a lubricant additive in reducing friction (Xu et al, 2015a;Hu et al, 2010;Wu et al, 2018;Liu and Zhou, 2017;Tang et al, 2013;Wang et al, 2023). However, MoS 2 nanoparticles are prone to…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation